The Influence of Customer Relationship Management on Loyalty Mediated by Customer Satisfaction and the Role of Service Quality as a Moderating Variable (Study at the Grand Mercure Malang Mirama Hotel) - Wibowo, Angelia (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to provide empirical evidence of the influence of Customer Relationship Management (CRM) on customer loyalty, mediated by customer satisfaction, and to examine the role of service quality as a moderating variable, with a case study conducted at Grand Mercure Malang Mirama Hotel. A quantitative approach with an associative design was employed. The population in this study comprises all customers who have stayed at the hotel. Sampling was conducted using purposive sampling, and the sample size was determined to be 96 respondents. The study applied a path analysis model with the assistance of Smart-PLS 4 software. The results indicate that: (1) Customer Relationship Management (CRM) has a positive and significant effect on both customer satisfaction and customer loyalty; (2) Customer satisfaction and service quality have a positive and significant influence on customer loyalty; (3) Customer satisfaction mediates the relationship between CRM and customer loyalty; and (4) Service quality does not significantly moderate the relationship between customer satisfaction and customer loyalty at Grand Mercure Malang Mirama Hotel.